Endemic fungal infections in solid organ and hematopoietic cell transplant recipients enrolled in the Transplant‐Associated Infection Surveillance Network (TRANSNET). Issue 2 (4th March 2014) - Kauffman, C.A.; Freifeld, A.G.; Andes, D.R.; Baddley, J.W.; Herwaldt, L.; Walker, R.C.; Alexander, B.D.; Anaissie, E.J.; Benedict, K.; Ito, J.I.; Knapp, K.M.; Lyon, G.M.; et al.
Abstract Background Invasive fungal infections are a major cause of morbidity and mortality among solid organ transplant (SOT) and hematopoietic cell transplant (HCT) recipients, but few data have been reported on the epidemiology of endemic fungal infections in these populations. Methods Fifteen institutions belonging to the Transplant‐Associated Infection Surveillance Network prospectively enrolled SOT and HCT recipients with histoplasmosis, blastomycosis, or coccidioidomycosis occurring between March 2001 and March 2006. Results A total of 70 patients (64 SOT recipients and 6 HCT recipients) had infection with an endemic mycosis, including 52 with histoplasmosis, 9 with blastomycosis, and 9 with coccidioidomycosis. The 12‐month cumulative incidence rate among SOT recipients for histoplasmosis was 0.102%. Occurrence of infection was bimodal; 28 (40%) infections occurred in the first 6 months post transplantation, and 24 (34%) occurred between 2 and 11 years post transplantation. Three patients were documented to have acquired infection from the donor organ. Seven SOT recipients with histoplasmosis and 3 with coccidioidomycosis died (16%); no HCT recipient died. Conclusions This 5‐year multicenter prospective surveillance study found that endemic mycoses occur uncommonly in SOT and HCT recipients, and that the period at risk extends for years after transplantation.